Nonuniform broadband circularly polarized antenna array for vehicular communications - Varum, Tiago (2017)
Road safety applications drive the development of vehicular communications as support to intelligent transport systems. The communications network necessary for this is supported by dedicated short-range communications (DSRC), which is based on roadside units (RSUs) and onbo ard units. In the RSU, the DSRC physical-layer standards, along with practical issues, require specific radiation patterns of the respective antenna, leading to the use of unusual arrays of antennas. This paper describes a new concept based on a binomial array structure, which simplifies the design of the antenna array while ensuring good performance. The new structure developed for this antenna enabled the design of a feed network using unbalanced power dividers in the same plane as that of the radiating elements, maintaining the favorable characteristics of microstrip antennas.